(untitled) (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: Suicide is one of the leading causes of death in young people. Therefore, suicide prevention in this age group is a public health priority. There is increasing evidence of the efficacy of suicide prevention programmes, but robust empirical studies are still needed. More precisely, data are needed for school-aged children, brief interventions and distal outcomes such as psychological distress or suicidal thoughts. In addition, to our knowledge, no study has yet scientifically evaluated a brief universal suicide prevention programme in Switzerland. This study investigated the efficacy and acceptability of a brief universal suicide prevention programme for school-aged youths. Primary outcomes included knowledge on suicide, perceived suicide awareness and knowledge of help-seeking resources. Secondary outcomes included acceptability coping skills, suicide-related behaviours and psychological distress. METHODS: This non-randomised cluster-controlled trial was conducted in Swiss schools. A 90-minute workshop for universal suicide prevention was delivered to the intervention group (n = 209), and the control group had no intervention (n = 96). Measures were assessed at baseline and after one month. Acceptability was assessed at follow-up in the intervention group only. Data were analysed using three-level mixed effect models with an interaction term between group and time. RESULTS: There were interaction effects between group and time for most outcomes: perceived suicide awareness (p <0.010), knowledge of help-seeking resources (p <0.001), coping planning (p = 0.039), suicidal ideation (p = 0.019) and psychological distress (p = 0.012). There were no interaction effects on suicide-related knowledge (p = 0.312) and coping for social support (p >0.388). Participants found the workshop enjoyable, not upsetting, and worthwhile. CONCLUSIONS: This study suggested that a brief suicide prevention programme could be beneficial and safe for school-aged youths. This brief programme may contribute to suicide prevention efforts.